INFORMATIVE COMPTENCE AS A COMPONENT OF TEACH - Sharko В.Д. (Journal of Information Technologies in Education (ITE), 2010)
Possibilities of forming of informatics’ competence are considered as a professional competence component of future physics teacher in Universities